The construal of experience in HCI: Understanding self-reports. Issue 110 (February 2018) - Doherty, Kevin; Doherty, Gavin
Highlights: Self-reports are commonly applied in HCI but differ in the aspects of experience which they access. Presents a framework for understanding fundamental differences between retrospective and momentary assessments. Illustrated with examples in health and wellbeing, guidelines on usage of different forms of self-report. Abstract: Design is driven by our understanding of users' experiences. This understanding rests primarily upon users' reports of their experiences, in the moment, after the fact, or ahead of time. In this paper we ask how the study of and design for experience might be better informed by attending more carefully to differences between these reports. Based on a broad and interdisciplinary literature review, we develop a conceptual framework of multiple selves, each representing a stage in the consolidation of experience accessed by self-report. We explore the use of this framework to support the interpretation of user experience, provide insight into users' evaluations of their own experiences, and emphasise the importance of design for experience as lived and reflected upon. We discuss the implications of this framing of experience for design, particularly in the case of systems to support self-knowledge, wellbeing, behaviour change, reflection, and decision making.